Increasing Risk of Disturbed Root Development in Permanent Teeth in Childhood Cancer Survivors Undergoing Cancer Treatment at Older Age. Issue 3 (April 2017) - Tanaka, Miyuki; Kamata, Takahiro; Yanagisawa, Ryu; Morita, Daisuke; Saito, Shoji; Sakashita, Kazuo; Shiohara, Masaaki; Kurita, Hiroshi; Koike, Kenichi; Nakazawa, Yozo
Abstract : Background: Structural anomalies of teeth are observed at high rates in childhood cancer survivors (CCS). Several therapeutic exposures have been shown to be associated with dental developmental disturbances. This study was conducted to analyze the risk factors for dental developmental abnormality (DDA) and investigate the association between age at the time of cancer treatment and DDA in CCS. Patients and Methods: Fifty-six CCS were enrolled. Orthopantomography and dental examination were performed in all the patients. We evaluated the prevalence of DDA and analyzed the risk factors for each type of DDA. Results: DDAs were observed in 46.4% of CCS, including hypodontia in 9 (16.1%), abnormal roots in nine (16.1%), enamel defects/hypoplasia in 6 (10.7%), and microdontia in 12 (21.4%) patients. The number of patients with abnormal roots was significantly higher in the group treated with stem cell transplantation or at an age older than 4 years. We observed that the formation period of abnormal teeth coincided with the treatment period in the majority of CCS with DDA. Conclusions: Particularly regarding the root abnormality, treatment at elder age may be a risk factor for root developmental disturbances. Risk evaluation, appropriate follow-up, and early detection of dental issues are required for all CCS.